OLIVA: a transversal analysis of indexed scientific production in Latin America. Disciplinary diversity, institutional collaboration, and multilingualism in SciELO and Redalyc - Beigel, Fernanda (2022)
The article addresses a complete corpus of scientific publications from Latin America and the Caribbean based on the consolidation of the records of the databases of journals indexed in SciELO and Redalyc for the period 1909-2019. This corpus is made up of almost 800,000 articles and more than 2,500,000 authors. 1720 journals from 15 countries are analyzed, along with their publishing institutions, highlighting the importance of universities and public institutions in the regional publishing circuit. The study highlights the magnitude of this circuit, its disciplinary diversity and observes the main trends in national and international collaboration. A particular focus is placed on the collaboration within the journals edited in Brazil- based on the SciELO database – analyzing the interaction between different States. This confronts the traditional reading of national collaboration as merely endogamic. English version: https://doi.org/10.1590/SciELOPreprints.4637